(untitled) (ICADE. Revista de la Facultad de Derecho, 2012)
Autores: Marta Gisbert Pomata, Sara DíezRiaza, Cristina González Carretero,Verónica González-Choren Respaldiza Editorial: Thomson Reuters, Madrid 2008, 692 páginas